Optimization of Extraction Method of Bioactive Compounds from Elderberries (Sambucus nigra L.) and Testing Extract Stability - Pascariu, Oana-Elena (2024)
Phenolic compounds from elderberries (Sambucus nigra L.) have attracted attention due to their potential health benefits. This paper examines different extraction methods used to obtain phenolic compounds from these fruits and the stability of the extracts. Several extraction techniques (extraction with continuous agitation, ultrasound-assisted extraction, microwave-assisted extraction, maceration, and enzyme-assisted extraction) were tested and compared to evaluate the yield and the quality of the extracts. The stability of the extracts with various storage parameters (time and temperature) and processing conditions (concentration and lyophilization) was also investigated. The results showed that ultrasound-assisted extraction (UAE) provided the highest yield of total phenolic compounds (74.89 mg GAE/g), of which 71.23% were represented by total anthocyanins and 62.50% by monomeric anthocyanins, with total flavonoids of 8.11–9.41 mg RUE/g. The analysis of individual phenolic compounds reconfirms the efficiency of UAE, obtaining 0.42–0.09 mg/g gallic acid, 0.59–0.01 mg/g chlorogenic acid, 0.17–0.03 mg/g 4-coumaric acid, and 2.43–0.01 mg/g rutin. The optimization of the extraction conditions led to the conclusion that the best solvent is 45% ethanol (v/v), and the optimal parameters are 40 ◦C for 40 min. It was also found that the stability of the extracts can be high during long periods of time (even after 180 days). These findings contribute to the understanding of the optimization of extraction processes and storage conditions to obtain extracts rich in phenolic compounds from elderberries, with potential uses in pharmaceutical and food applications.